Direct analytical parameter extraction for SiGe HBTs T-topology small-signal equivalent circuit. (June 2016) - Sun, Yabin; Fu, Jun; Wang, Yudong; Zhou, Wei; Zhang, Wei; Liu, Zhihong
Abstract: In this paper, an accurate direct analytical method to extract the model parameters in SiGe HBT T-topology small-signal equivalent circuit is presented. After the pad parasitics and extrinsic circuit elements are determined and removed from the measured S -parameter, the admittance matrix of intrinsic HBT in common-emitter configuration is derived in the form of non-linear rational function, as a function of angular frequency. Eight constants are accurately obtained based on the non-linear rational function fitting over the whole range of frequencies. Then the intrinsic circuit elements are directly determined in an analytical closed-form manner without any numerical optimization or special test structure. The proposed technique is successfully validated with several sized SiGe HBTs from 100 MHz to 20.89 GHz, and excellent agreement is obtained between the measured and simulated S -parameters over the whole frequency range. Highlights: Substrate parameters are extracted and the bias dependence are modeled from discrete measured points. Admittance matrix for intrinsic HBT are derived in the form of non-linear rational function. Eight constant terms are obtained and intrinsic elements are accurately extracted in an analytical closed-form manner. Proposed method is validated and the simulated S-parameter match well with the measured data in desired frequency range.